2017
DOI: 10.1111/aej.12230
|View full text |Cite
|
Sign up to set email alerts
|

A comparative in vitro study of different techniques for removal of fibre posts from root canals

Abstract: This study evaluates the effectiveness of different techniques to remove fibre posts from root filled teeth in vitro. One hundred and fifty-three extracted single-rooted teeth were decoronated, root-canal treated and divided into three groups (n = 51). Post spaces were prepared for different types of fibre posts: glass fibre, quartz fibre, carbon fibre. Each group was divided into three subgroups with regard to the post removal technique (n = 17): SonicFlex Endo, long-shaft round bur, DT-Post removal kit. Resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 17 publications
(35 reference statements)
1
26
1
9
Order By: Relevance
“…Later, it was advised to use long‐shank endo burs combined with optical aids, as an operating microscope. However, these latter techniques also entailed iatrogenic risk because of the strong likelihood of misdirecting the drill and perforating the root . Furthermore, most dentists are not equipped with adequate optical aids to ensure safe removal of fibre posts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it was advised to use long‐shank endo burs combined with optical aids, as an operating microscope. However, these latter techniques also entailed iatrogenic risk because of the strong likelihood of misdirecting the drill and perforating the root . Furthermore, most dentists are not equipped with adequate optical aids to ensure safe removal of fibre posts.…”
Section: Discussionmentioning
confidence: 99%
“…The various techniques for fibre post removal all entail risks, as Haupt et al . showed . These authors reported a high prevalence of root perforation, axis deviation and consequent fragilisation of the roots, entailing a poorer survival prognosis for the tooth.…”
Section: Introductionmentioning
confidence: 98%
“…Successful endodontic retreatment requires efficient removal of the posts without leaving residual materials on the root canal walls. Haupt, Pfitzner, and Hülsmann () reported that removal kits left more residue on the root canals than burs and sonic tips, regardless of fiber post type. Lindemann et al () compared the efficiencies of a fiber post removal system recommended by the manufacturer and ultrasonic tips.…”
Section: Discussionmentioning
confidence: 99%
“…Protection of the root structure is important for sufficient root resistance and long‐term tooth retention. Haupt et al () compared the D.T. Light‐Post removal kit, burs, and sonic tips in the removal of glass, carbon, and quartz fiber posts; they reported that burs removed more material from the dentin, and the least loss occurred when quartz fiber posts were used with dismantling kits.…”
Section: Discussionmentioning
confidence: 99%
“…It has been studied that the removal of carbon posts generally took a longer time for removal when compared to glass and quartz fibre posts. It was also found that there was higher risk for root perforation during the removal of fibre posts [ (Haupt, Pfitzner and Hülsmann, 2018)]. Capar et al, found that fibre post removals with drills does not does not have a significant effect on crack propagation [ (Çapar et al, 2015)].…”
Section: Resultsmentioning
confidence: 99%